Performance Analysis of Model-Based Control for Thermoelectric Window Frames - Zhineng He; César Martín-Gómez; Amaia Zuazua-Ros (Buildings)
The Thermoelectric Window Frame (TEWF) can be adjusted by regulating the operating current to achieve the desired indoor temperature. However, indoor and outdoor ambient disturbances are inevitable, causing indoor temperature fluctuations and preventing them from reaching the set point. To solve the problem, a model-based control method is proposed to maintain the indoor temperature at the set point in this work. This method relies on a computational model for determining the operating current and a transient model for tracking variations in indoor temperature. Experimental results under various working conditions validate the two models. Moreover, indoor interference (e.g., changes in set point or air leaks due to occupants’ behavior) and outdoor interference (e.g., changes in the outdoor temperature) are incorporated into stable-state experiments. When these interferences occur, new operating currents are calculated for the new working conditions and applied to the TEWF. The results show that the indoor temperature significantly deviates from the desired values if the operating currents are not adjusted when disturbances occur. However, the indoor temperature can reach the set point by regulating the new operating currents in time, even during disturbances.